Experiences in the use of a media space - Mantei, M. M.; Baecker, R.; Sellen, Abigail; Wellman, B.; Buxton, Bill (Proceedings of CHI '91, New Orleans, LA., 1991)
A media space is a system that uses integrated video, audio, and computers to a How individuals and groups to work together despite being distributed spatially and temporally. Our media space, CAVECAT (Computer Audio Video Enhanced Collaboration And Telepresence), enables a small number of individuals or groups located in separate offices to engage in collaborative work without leaving their offices. This paper presents and summarizes our experiences during initial use of CAVECAT, including unsolved technological obstacles we have encountered, and the psychological and social impact of the technology. Where possible we discuss relevant findings from the psychological literature, and implications for design of the next-generation media space.